2020
DOI: 10.1242/bio.052043
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest cells require Meis2 for patterning the mandibular arch via the Sonic hedgehog pathway

Abstract: Cranial neural crest cells (cNCCs) originate in the anterior neural tube and populate pharyngeal arches in which they contribute to formation of bone and cartilage. This cell population also provides molecular signals for the development of tissues of non-neural crest origin, such as the tongue muscles, teeth enamel or gland epithelium. Here we show that the transcription factor Meis2 is expressed in the oral region of the first pharyngeal arch (PA1) and later in the tongue primordium. Conditional inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…2 ) ( 92 , 93 ). A myeloid ecotropic insertion site 2 (MEIS2) transcription factor is another molecule that activates the expression of the SHH gene for patterning the mandibular arch during fetal development, as observed by Fabik et al ( 35 ) in a mouse model. The upregulation of MEIS2 was observed in castration-resistant prostate cancer (PC) ( 94 ) and hepatocellular carcinoma, where its isoform MEIS2C activates the Wnt/β-catenin pathway by interacting with the CDC73 molecule ( 95 ).…”
Section: Role Of Micrornas (Mirnas/mirs) In Upstream Shh Gene Regulationmentioning
confidence: 97%
See 1 more Smart Citation
“…2 ) ( 92 , 93 ). A myeloid ecotropic insertion site 2 (MEIS2) transcription factor is another molecule that activates the expression of the SHH gene for patterning the mandibular arch during fetal development, as observed by Fabik et al ( 35 ) in a mouse model. The upregulation of MEIS2 was observed in castration-resistant prostate cancer (PC) ( 94 ) and hepatocellular carcinoma, where its isoform MEIS2C activates the Wnt/β-catenin pathway by interacting with the CDC73 molecule ( 95 ).…”
Section: Role Of Micrornas (Mirnas/mirs) In Upstream Shh Gene Regulationmentioning
confidence: 97%
“…Recent research on genomic DNA of patients affected by holoprosencephaly has revealed that eight synonymous single-nucleotide variants in the SHH gene are associated with a reduced level of SHH protein ( 34 ). A recent in vivo study on Cre-modified mice demonstrated that SHH expression was also crucial for proper fetal development of the tongue and mandible ( 35 ). SHH is the most well-known among other hedgehog family proteins, comprising Desert Hedgehog (DHH) and Indian hedgehog (IHH) molecules ( 36 ).…”
Section: Mammalian Sonic Hedgehog Canonical Pathwaymentioning
confidence: 99%
“…The elimination of Meis2 specifically in NCCs results in extensive craniofacial defects [ 78 ]. Furthermore, NC-specific Meis2 embryonic mutants have elevated osteogenesis in the mandibular and hyoid arch at the expense of disrupted tongue development [ 79 ]. Craniofacial defects in the maxillary and mandibular processes of Meis2 -deficient embryos thus reveal the Hox-independent function of Meis2.…”
Section: Specification Of Mandibular and Hyoid Arches By The Meis/pbx Complexmentioning
confidence: 99%
“…Craniofacial defects in the maxillary and mandibular processes of Meis2 -deficient embryos thus reveal the Hox-independent function of Meis2. Furthermore, altered osteogenesis within the hyoid arch also results in various defects of the hyoid apparatus in Meis2 -deficient embryos [ 78 , 79 ]. The MEIS–PBX–HOX regulatory circuit seems to be evolutionary conserved.…”
Section: Specification Of Mandibular and Hyoid Arches By The Meis/pbx Complexmentioning
confidence: 99%
See 1 more Smart Citation